Assessment of the Primary and Intermediate School Staffs’ Knowledge, Attitude and Practice on Care of Children with Type 1 Diabetes at School, Al-Jouf, Saudi Arabia - Al Duraywish A A; Abdelsalam M Nail (Sudan Journal of Medical Sciences)
Background: Children with diabetes type 1 (T1DM) need close monitoring for their blood glucose, food intake, insulin therapy and physical activity during school hours in order to guard against the development of acute and long-term complications.